Karakteristik Fisik Lignin pada Serat Tandan Kosong Kelapa Sawit PT. Tunggal Perkasa Plantataions Provinsi Riau Menggunakan Metode Organosolv - Angga Pramana; Muhammad Nur Cahyanto; Heni Adhianata; Yelmira Zalfiatri (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2020)
Oil palm empty fruit bunches (OPEFB) are solid waste from the palm industry that contains linocellulose in the form of lignin, cellulose and hemicellulose. Lignin using as a binder, adhesive, filler, surfactant, polymer product, dispersant and source of ingredients. The method of isolating lignin can be done by the organosolv method. In the organosolv process, temperature is a factor that will affect the speed of the lignin dissolution reaction. This study aims to determine the physical characteristics of oil palm empty fruit bunches of PT. Tunggal Perkasa Plantations, Regency of Indragiri Hulu, Riau Province. In the study conducted effect of cooking temperature on the isolation process of OPEFB with the organosolv method using acetic acid solvents with 0.1% HCl catalyst. The experimental design used in this study was a Completely Randomized Design consisting of 4 treatments  temperature of  cooking  (60°C,  85°C,  100°C  and  121°C).  L value indicates the brightness of lignin, the higher the L value means that the color of lignin is brighter. The value of Lignin at  100 ̊C was  35.14 while the value of L lignin at 121 C  was  32.245. If  ‘a’ values indicate lignin redness and  ‘b’ values indicate yellowish. The highest yield of OPEFB lignin was obtained using a temperature of 85 °C is 15.87%.